Chemical structures of constituents from the seeds of Cassia auriculata. Issue 38 (23rd September 2015) - Zhang, Yi; Nakamura, Seikou; Nakashima, Souichi; Wang, Tao; Yoshikawa, Masayuki; Matsuda, Hisashi
Abstract: Five new diterpene glycosides, auricuosides I (1 ), II (2 ), III (3 ), IV (4 ), and V (5 ), a new flavonol glycoside, auricuoflavonoside I (6 ), and a new megastigmane glycoside, auricuomegastigmane I (7 ), were isolated from the seeds of Cassia auriculata, together with 11 known constituents. The chemical structures of seven new constituents were characterized on the basis of chemical and physicochemical evidence. In the present study, auricuosides I (1 )–V (5 ) were obtained from the seeds of C. auriculata . To the best of our knowledge, there is no report about the isolation of kaurenolides with hydroxy group at 14-position from plants. This finding is interesting from the perspective of chemotaxonomy and biosynthesis of kaurenolide. Graphical abstract: